Aprovechamiento de los residuos orgánicos del relleno de Doña Juana para obtención de energía (2019)
Understanding the advanced increase and creation of waste in the world and the inevitable exhaustion of available space, moreover, of its effects to the environment and to the health of humans as animals and any be alive raised an alternative to the waste essentially organic waste which those who are most produce effects like smells, vectors, damage to the ground and others if they do not have in a good way.